2005
DOI: 10.1089/pho.2005.23.567
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Low Intensity Laser Effects on the Thyroid Gland of Male Mice

Abstract: It was concluded that low-level laser therapy (LLLT) of the thyroid gland may affect the level of thyroidal hormones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 8 publications
0
15
0
3
Order By: Relevance
“…En un claro antagonismo con este resultado, Azevedo et al (2005), trabajando en ratas Swiss albinas, estimularon tejido tiroideo con láser infrarrojo y dosis de 4 J/cm 2 y a través de microscopía óptica indicaron que no se producía ninguna modificación morfológica en el epitelio folicular, probando entonces que las modificaciones celulares o tisulares, producto de las estimulaciones, son extremadamente dependientes de las dosis utilizadas. Asimismo, Parrado et al (1990) probaron que existe una directa relación entre las eventuales modificaciones morfológicas y la energía de la radiación utilizada.…”
Section: Resultsunclassified
“…En un claro antagonismo con este resultado, Azevedo et al (2005), trabajando en ratas Swiss albinas, estimularon tejido tiroideo con láser infrarrojo y dosis de 4 J/cm 2 y a través de microscopía óptica indicaron que no se producía ninguna modificación morfológica en el epitelio folicular, probando entonces que las modificaciones celulares o tisulares, producto de las estimulaciones, son extremadamente dependientes de las dosis utilizadas. Asimismo, Parrado et al (1990) probaron que existe una directa relación entre las eventuales modificaciones morfológicas y la energía de la radiación utilizada.…”
Section: Resultsunclassified
“…Un nuevo ejemplo de efectos generados por inducciones de laser infrarrojo sobre tiroides es el trabajo de Azevedo et al (2005) quienes describen incrementos en la síntesis y secreción hormonales de T3 y T4 al estimular tiroides de ratones con dosis de 4 J/cm 2 . Sin embargo, AlMustawfi et al (2010) al estimular tiroides pertenecientes a conejos hembras con dosis infrarrojas de 4 J/cm 2 describen Tabla II.…”
Section: Discussionunclassified
“…5,6,[28][29][30]36,38 The rabbit model was chosen because of the previously reported ease of handling, surgical preparation, and postoperative follow-up. 8,28,34,38 Moreover, the size of these animals enabled the use of conventional implants available for clinical use in humans. As for implant placement in fresh tooth extraction sockets, we chose this method of implant placement, rather than the tibia (which is the most common site reported in the literature), in order to provide the closest possible simulation of a clinical situation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the effect of infrared laser irradiation directly on the thyroid gland have shown increased mitotic activity in follicular cells, transient hyperactivity of some thyroid follicles, 32,33 and changes in circulating serum levels of the hormones secreted by the thyroid gland, triiodothyronine (T3) and thyroxine (T4). [34][35][36] These findings prompted the present study, as the thyroid gland is located near the mandibular region, a frequent site of irradiation after dental procedures. The objective of this study was to assess the side effects or systemic effects of LLLT used after mandibular dental implant insertion to improve osseointegration through a systematic assessment of circulating serum levels of T3, T4, and calcium in a rabbit model after three different protocols of low-level laser irradiation of the area of implantation of the osseointegrated implant placed immediately into the fresh extraction socket of the mandibular left incisor.…”
Section: Introductionmentioning
confidence: 92%